The origin of nasality in Macedonian dialects - Sawicka, Irena (Vilnius University Open Series, 2021)
There is general consensus that the southern Macedonian dialects have partially retained the Proto-Slavic nasal vowels, and that the preservation was favoured by local Greek phonetics. There was, however, an additional source of (non-etymological) nasality in Macedonian – the Greek pre-nasalisation of stops. In the article, I would like to re-examine this issue in terms of the hypothesis that the source of nasality in Macedonian dialects was not the old nasal vowels, but the Greek pre-nasalisation of stops.